Application of Digital Technology in Educational Administration at Madrasah Mu'allimin Mu'allimat Bahrul Ulum Jombang - Fitria, Ni’mah; Wiyono, Bambang Budi (Proceedings Series of Educational Studies, 2025)
Education is the foundation of a quality civilization. The importance of technology in the world of education is increasingly felt as the times develop. This article discusses the application of technology and administrative systems at Mu'allimin Mu'allimat Bahrul Ulum Jombang school which still holds tight to its traditional culture but still strives to adapt to technological advances. The research used is qualitative which aims to explore the strategies applied in integrating technology, such as the development of the SIM (Madrasah Information System) website and the Mu'alliminEnamTahun.Net website to be able to improve administrative efficiency and communication between schools and student guardians. The results show that the application of technology not only speeds up and simplifies the process, but also increases data security and information transparency. However, challenges in teacher motivation and lack of training remain. Overall, the application of technology has had a positive impact on improving school quality.